THE EFFECT OF SUPPLEMENTAL LIGHT ON MILK PRODUCTION IN HOLSTEIN DAIRY COWS - C. GAVAN; V. MOTORGA (Scientific Papers Animal Science and Biotechnologies, 2023)
20 multiparous cows were utilized to investigate effect of supplemental light on milk production. Cows were randomly assigned to one of two treatments (n=10): a) 10- 13 hours of light and 14-11 hours of darkness/d natural light -NL group; b) 17 hours of light (natural light + supplemental light) -SL group. Supplemental lighting of 350 lx at eye level was provided by fluorescent lamps, controlled by an automatic timer. Multiparous cows in SL group produced more fat corected milk (FMC) than multiparous cows in NL group. The efficiency of production in dairy cows can be enhanced by the photoperiod manipulation and thus provide another management tool for dairy producers to enhance productivity.